Didactic approach to the process of communicative competence formation - Petrova, M.; Uteubayeva, E.A.; Kokhanover, T.A. (KU publ., 2020)
Article is devoted to studying of the didactic approach to teaching foreign languages. One of the key elements of foreign languages teaching is didactic approach, which organize and manage the process of teaching and is aimed at achieving the best result. It is very important to chose the appropriate didactic principles and organize its activity in pedagogical process. As a result of analyses of Russian and foreign methodologist in the article we made the attempt to elicit and prove the main and effective principles of didactic approach to improve the communicative competence of the learners in the conditions of trilingual education.
Коммуникативтік құзыреттілікті қалыптастыру процесінің дидактикалық шарттары
Дидактические условия процесса формирования коммуникативной компетенции
Keywords: didactic approach; principles; communicative competence; foreign languageteaching; activity; integrated teaching; individualization; communicative approach